Emotional intelligence and its association with dental anxiety in children: Literature review - Manrique-Mamani, Estefany Karen (2024)
Objective: To review information regarding to Emotional Intelligence (EI) and its association with dental anxiety in children. Material and Methods: A bibliographic search was conducted in the Scopus, Pubmed, SciELO and Google Scholar databases. The descriptors “Emotional Intelligence”, “Dental Anxiety” and “Child” used were for search. Selection criteria included articles published in English, Spanish and Portuguese. Likewise, cross-sectional studies, cohort studies, case-control studies, andrandomized controlled clinical studies were included. Literature reviews, systematic reviews and metaanalyses, letters to the editor and Book chapters were excluded; and no restriction on years of publication was made. A total of 31 articles were identified in the databases. Subsequently, two researchers independently selected the articles by searching the titles and reading the abstracts and duplicates. Finally, four articles were included in the literature review. Conclusion: Children with high levels of emotional intelligence could present less anxiety and cope better with dental procedures.